Music Representation and Transformation in Software: Structure and Algorithms in Python - Pazel, Donald P (Springer International Publishing AG, 2022)
This book takes the reader on a journey through music concepts in an organized approach that develops music essentials from the concepts of tone, pitch, and time, through notes, intervals, chords, and scores while at the same time interpreting these elements as software artifacts.